2012
DOI: 10.2165/11634580-000000000-00000
|View full text |Cite
|
Sign up to set email alerts
|

Topical Rapamycin Therapy to Alleviate the Cutaneous Manifestations of Tuberous Sclerosis Complex

Abstract: Background and ObjectivesFacial angiofibromas are disfiguring facial lesions, present in up to 80% of patients with tuberous sclerosis complex. Recent elucidation of the complex cell signaling pathways that are disrupted in tuberous sclerosis indicates that rapamycin may be successful in alleviating the appearance of these lesions. The objectives of the current study were to evaluate the safety of topically applied rapamycin in patients with tuberous sclerosis complex and to determine its potential effectivene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
44
0
4

Year Published

2013
2013
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 121 publications
(50 citation statements)
references
References 26 publications
2
44
0
4
Order By: Relevance
“…Several studies have reported that sirolimus plasmatic concentration remains undetectable even in daily application (3,5,6,10,11). These determinations were not made in our patients.…”
Section: © C I C E D I Z I O N I I N T E R N a Z I O N A L Imentioning
confidence: 68%
“…Several studies have reported that sirolimus plasmatic concentration remains undetectable even in daily application (3,5,6,10,11). These determinations were not made in our patients.…”
Section: © C I C E D I Z I O N I I N T E R N a Z I O N A L Imentioning
confidence: 68%
“…Since Haemel et al [6] first reported improvement of facial angiofibromas after applying 1% rapamycin ointment twice daily, several papers have reported the use of topical rapamycin to treat facial angiofibromas [2,3,4,5,6,7,8,9,10,11] (table 1). Although varying levels of improvement were recorded in the previous studies, most reported no significant systemic or local side effects during the treatment period (6 weeks to 9 months).…”
Section: Discussionmentioning
confidence: 99%
“…The concentration, vehicle material, application frequency and total treatment period differed among the studies. With regard to the concentration of ointment or solution, all previous studies reported clinical improvement with concentrations ranging from 0.003 to 1.0% in different vehicles [2,3,4,5,6,7,8,9,10,11]. Foster et al [7] demonstrated that topical rapamycin treatment had the same effect whether it was in an ointment base or in a water base, although the ointment base caused less skin irritation than the water base.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations